2013
DOI: 10.5463/dcid.v23i4.155
|View full text |Cite
|
Sign up to set email alerts
|

Community-based Physiotherapy in Western India: Some Findings from Surveys

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 5 publications
2
12
0
Order By: Relevance
“…This is not a new finding as it has been noted in previous studies on Indian physiotherapy students (Rajan, 2012(Rajan, , 2013. Community Health was the second preferred specialisation, which is indeed a finding unique to this study; previous studies in India having reported Community Physiotherapy as a neglected profession (Rajan, 2012(Rajan, , 2013.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…This is not a new finding as it has been noted in previous studies on Indian physiotherapy students (Rajan, 2012(Rajan, , 2013. Community Health was the second preferred specialisation, which is indeed a finding unique to this study; previous studies in India having reported Community Physiotherapy as a neglected profession (Rajan, 2012(Rajan, , 2013.…”
Section: Discussionmentioning
confidence: 52%
“…This is not a new finding as it has been noted in previous studies on Indian physiotherapy students (Rajan, 2012(Rajan, , 2013. Community Health was the second preferred specialisation, which is indeed a finding unique to this study; previous studies in India having reported Community Physiotherapy as a neglected profession (Rajan, 2012(Rajan, , 2013. This could again be due to the opportunities that students have at this particular training institute, to gain knowledge and foster their interests (Jeffe et al, 1998;Latimer et al, 2004).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Community Physiotherapy in India needs attention, since there is an imbalance between the demand and supply in this field (Rajan, 2012a(Rajan, , 2012b(Rajan, , 2014. Although this specialisation has been offered for many years, the pool of physiotherapists willing to work with the communities has not increased as per the need.…”
Section: Introductionmentioning
confidence: 99%
“…These discussions helped to understand the prevalent musculoskeletal health issues in this cohort; thereafter, community physiotherapy was recommended for these problems. In an earlier study by Rajan (2012), focus group discussions were used to look into the lacunae in the community physiotherapy system in western India. While focus group discussions and interviews have proved to be effective in understanding community physiotherapy issues, studies on the subject are few.…”
mentioning
confidence: 99%